(untitled) (Journal of Global Accounting, 2023)
The purpose of this study is to examine the relationship between board size and tax compliance in listed industrial good firms in Nigeria. The focus was on the industry due to its importance to the Nigerian economy. The study adopts ex post facto research design. Data sourced from published 2016 – 2020 financial statements of 13 purposely selected firms from the industry were analysed with Random Effect Model, confirmed by Hausman test. Board size was proxy with number of board members while tax compliance was proxy with effective tax rate. Findings from the results of analysis revealed that board size has a significant positive relationship with tax compliance. Since board size has a positive and significant relationship with tax compliance, the study recommends to corporate organisations that the size of board of directors should be properly constituted. It also recommends that government and relevant tax authorities should put in place policies that will encourage tax compliance.